REPRESENTASI PEREMPUAN SEBAGAI SIMBOL PERLAWANAN PADA NOVEL JALAN PANJANG MENUJU PULANG KARYA PIPIET SENJA: KAJIAN FEMINISME RADIKAL - Suci Annisa Caroline; Novi Anoegrajekti; Heru S.P. Saputra (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2019)
In a dominant patriarchal culture, women are considered lower than men in many aspects such as education, politics, workplace, and the sexuality discourse. This article shows the representation of women who symbolize her resistance which is reflected in the novel entitled Jalan Panjang Menuju Pulang by Pipiet Senja. It is used qualitative method supported by descriptive analysis on the basis of theoretical of radical feminism. The results of the study show that woman (Fatin) is subjugated by men. There are physical violence, psychological violence, and also domestic violence which happened to Fatin. Hans did Sexual harassment, while sexual violence done by Frankie. Meanwhile her husband ,Rimbong, threat her and hit her. Fatin suffers psychic and also physical violence. This spouse fought for the custody right. This research discuss about how Fatin showing her resistance to the domestic violence and sexual violence. In her apartment, Fatin dares to scuffles then reports Frankie to the police. She also reveals her resistance by hiding away her child when her husband will take her child.